Management of peer-to-peer overlays. (7th July 2008) - Buford, John F.
Peer-to-peer overlays constitute a new approach for delivering wide-area network and application services. The systems typically use a combination of self-organisation and cooperation with other peers to determine the peer's role and performance in the overlay. Few overlays support external management mechanisms, which are the basis for overlay operators to provide specified service levels. We present a general model for supporting service assurance, provisioning, and diagnostics in large scale overlays which retains the self-organising properties of the overlay. We describe the operations with detailed examples, and assess the message overhead needed for overlay management vs. operational overhead.